Effects of fragmentation and hybridization on geographical patterns of song variation in the endangered Yellow Cardinal Gubernatrix cristata - Dominguez, Marisol (2016)
The song learning process may lead to small-scale geographical variation in vocalizations of oscine birds. This variation can be further enhanced by the effects of habitat fragmentation or hybridization. Populations of the endangered Yellow Cardinal Gubernatrix cristata are now patchily distributed in the southern South American thorny shrubland forests and are small as a consequence of the pressure exerted by increased habitat transformation and illegal trade. We study the Yellow Cardinal's vocalizations throughout its distribution and assess how habitat characteristics and fragmentation, as well as hybridization with the Common Diuca Diuca diuca, have affected song patterns of different populations. We expected to find song differences among populations and songs to be more similar to those of the Common Diuca in areas where hybridization occurs. Multivariate analyses revealed significant differences in song between the four populations studied and confirmed that songs are more similar to those of Common Diuca where hybridization takes place. These results, in conjunction with genetic studies, can help to establish management units that preserve genetic and cultural variation in this endangered species.